2016
DOI: 10.1186/s40665-016-0018-z
|View full text |Cite
|
Sign up to set email alerts
|

Trust, tribalism and tweets: has political polarization made science a “wedge issue”?

Abstract: Background: Political polarization remains a major obstacle to national action on global climate change in the United States Congress, and acceptance of anthropogenic drivers strongly differs between Republicans and Democrats. But has overall interest in science also become ingrained into partisan identity, even among national political figures tasked with making ostensibly science-based policy decisions? Social media outlets such as Twitter have become a popular means of exchanging information and of portrayi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The rate of recent warming is also highly anomalous in the global record back to 1900 (Pershing et al, 2015), with the number of "surprisingly" hot years increasing faster than expected (Pershing et al, 2019). Scientific consensus does not mean public support, and political polarization around climate change persists in the United States (Hamilton, 2011;Helmuth, Gouhier, Scyphers, & Mocarski, 2016 However, while modern observations were also mixed in terms of willingness to attribute warming to climate change, articles citing climate change were generally written in a more authoritative, confirmatory tone than those from the past (Table 2). Scientific consensus does not mean public support, and political polarization around climate change persists in the United States (Hamilton, 2011;Helmuth, Gouhier, Scyphers, & Mocarski, 2016 However, while modern observations were also mixed in terms of willingness to attribute warming to climate change, articles citing climate change were generally written in a more authoritative, confirmatory tone than those from the past (Table 2).…”
Section: Global Warming: Then and Nowmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of recent warming is also highly anomalous in the global record back to 1900 (Pershing et al, 2015), with the number of "surprisingly" hot years increasing faster than expected (Pershing et al, 2019). Scientific consensus does not mean public support, and political polarization around climate change persists in the United States (Hamilton, 2011;Helmuth, Gouhier, Scyphers, & Mocarski, 2016 However, while modern observations were also mixed in terms of willingness to attribute warming to climate change, articles citing climate change were generally written in a more authoritative, confirmatory tone than those from the past (Table 2). Scientific consensus does not mean public support, and political polarization around climate change persists in the United States (Hamilton, 2011;Helmuth, Gouhier, Scyphers, & Mocarski, 2016 However, while modern observations were also mixed in terms of willingness to attribute warming to climate change, articles citing climate change were generally written in a more authoritative, confirmatory tone than those from the past (Table 2).…”
Section: Global Warming: Then and Nowmentioning
confidence: 99%
“…The effects of warming on fisheries are also more clearly understood today, with a range of severe negative consequences commonly attributed to global warming, including hurricanes (Emanuel, 2005) and disease (Burge et al, 2014;Khasnis & Nettleman, 2005). Scientific consensus does not mean public support, and political polarization around climate change persists in the United States (Hamilton, 2011;Helmuth, Gouhier, Scyphers, & Mocarski, 2016). Moreover, studies have shown that while personal experiences with temperature anomalies can influence perceptions of local or regional weather trends, they do not generally trigger major shifts in beliefs related to global climate change (McCright, Dunlap, & Xiao, 2014).…”
Section: Global Warming: Then and Nowmentioning
confidence: 99%
“…The impacts of division within a society are widespread, affecting the stories and narratives that individuals choose to share 3,4 , their political affiliations and how they vote 5,11 , and even how society views scientific findings, e.g. Darwinian evolution versus intelligent design, and climate change 12 . On issues for which there is no counter-evidence, a surprisingly large number of people may still take an ‘anti-crowd’ viewpoint, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists are not seen universally as experts in their field by all segments of the population, and some scientific issues are politically polarized. Specifically, conservatives' trust in science has been steadily declining since at least the 1970s (Gauchat, 2012), and trust in science is increasingly seen as a Democratic value (Helmuth, Gouhier, Scyphers, & Mocarski, 2016). Although much of the academic literature is focused on stagnant or declining scientific literacy as a primary reason for mistrust in science, other explanations for scientific mistrust have been put forth, including the disconnection the public experiences from the creation and propagation of scientific knowledge (Habermas, 1989;Merton, 1973) and the general feeling of cultural and social discontent with contemporary society, which is perceived to be unpredictable and meaningless (Achterberg, de Koster, & van der Waal, 2017).…”
Section: Case Study: #Overlyhonestmethods On Twittermentioning
confidence: 99%